2008
DOI: 10.1007/s00384-008-0512-2
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic criteria for right colonic diverticulitis: prospective evaluation of 100 patients

Abstract: Performing CT scans after application of these diagnostic criteria gave a superior preoperative diagnostic rate for patients with RCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
3
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 16 publications
5
48
3
5
Order By: Relevance
“…Right-sided colonic diverticulitis has been reported to occur predominantly in relatively young males whereas left-sided diverticular disease is more common in women, with its incidence increasing with age [56789]. The present study also found that left-sided colonic diverticulitis was significantly associated with both older age and female sex.…”
Section: Discussionsupporting
confidence: 67%
“…Right-sided colonic diverticulitis has been reported to occur predominantly in relatively young males whereas left-sided diverticular disease is more common in women, with its incidence increasing with age [56789]. The present study also found that left-sided colonic diverticulitis was significantly associated with both older age and female sex.…”
Section: Discussionsupporting
confidence: 67%
“…1, 2 About 10-25% of the diverticulosis patients develop acute sigmoid diverticulitis in the course of their lives. [3][4][5] Epidemiological data show a disproportionately increased incidence in young patients. 14,20,23 The course and therapeutic regimen for these patients are still controversially discussed.…”
Section: Discussionmentioning
confidence: 99%
“…1, 2 About 10-25% of these patients develop acute sigmoid diverticulitis. [3][4][5] Its clinical spectrum extends from asymptomatic diverticulosis with recurrent courses to symptomatic disease with potentially fatal complications. 6 The indication for surgical intervention depends on several factors.…”
Section: Introductionmentioning
confidence: 99%
“…It can present a significant diagnostic challenge, especially with acute appendicitis (Fig. 5) [17, 18]. Actually, the clinical preoperative diagnosis rate of right CD is as low as 5–35% [17, 19].…”
Section: Pitfalls Related To Anatomical Factorsmentioning
confidence: 99%